Relative changes in body composition and functional capacities in regional youth soccer players 10 - 16 years - Vänttinen, T. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
In general, the changes in body composition and functional capacities that occur with chronological age during puberty in males is well documented (Malina 2004). In addition, Philippaerts & al. (2006) have shown that the peak development in functional capacities occurs around at time of peak height velocity among youth soccer players. Even though the peak height velocity is obviously independent from exact chronological age, the Finnish junior soccer teams are organized based on chronological age. Therefore, the aim of this study was to examine in which chronological age group the peak development of different body composition variables and functional capacities occurs. Methods. Three age groups (10y, 12y and 14y) of the regional club team (n = 12-14 players/team) representing area of around 160 000 habitants were followed two years in terms of body composition (height, weight; standard techniques, muscle mass; bioimpedance Inbody 720), hormonal status (testosterone; basal venous sample after 12 h fasting), speed (30 m; light cells), agility (8-track; light cells), explosive strength (CMJ; contact mat, 5-step; standard technique), isometric strength (legs 107º, abdominals, back; dynamometer) and soccer skills (passing and dribbling; skill tracks). Thus, in the present set-up age groups from 10y to 16y were covered so that the same players were followed from 10y to 12y, from 12y to 14y and from 14y to 16y. Results. The relative peak development in measured variable occurred between 10y to 11y in soccer skills (8.4 ± 2.6 %); between 12y to 13y in length (5.0 ± 1.7 %), weight (14.1 ± 4.6 %), muscle mass (15.2 ± 7.9 %), speed (5.2 ± 3.8 %) and agility (3.8 ± 2.6 %); between 13y to 14y in hormonal status (5.8 ± 5.5 nmol/l), CMJ (13.5 ± 10.4 %) and leg strength (24.1 ± 28.4 %); between 14y to 15y in 5-step (8.1 ± 4.2 %), abdominal strength (26 ± 16.5 %) and back strength (17.7 ± 12.7 %). No peak development was found between 11y to 12y or between 15y to 16y in any measured variables. Conclusions. The results of the present study suggested that the peak development during puberty in Finnish regional soccer players occurred first in the basic soccer skills followed by the changes in body composition and speed related tasks and finally in the explosive and maximal strength. From the results of the present study it can be recommended that the soccer training should focus on exercises which develop speed and basic soccer skills in early puberty. At the age of 14 years the players are ready to begin strength training and are hormonally more ready for "adult-like soccer training".